Analisis Pengetahuan tentang Donor Darah untuk Kesehatan di Kalangan Mahasiswa Universitas Sunan Giri Surabaya - Maytita Tri Hardiyanti; Dewi Sekar Arum; Allifia Hariaji; Rommy Hardyansah; Rahayu Mardikaningsih; Billy Sasmita; Didit Darmawan; Yuliani Yuliani; Desak Gede Sri Baktiasih; Ade Riyanto; Nurul Safitri (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Blood donation is an important process that involves taking some blood from a donor to donate and store it in a blood bank. This blood can then be used for transfusions for those in need, such as in cases of accidents, major surgery, or certain illnesses. In Indonesia, blood donation is very important, especially because of the high maternal mortality rate due to bleeding during childbirth. The need for blood continues to increase as the number of accidents and illnesses requiring blood transfusions increases. Although blood donation has great benefits for the recipient, many people do not realize that donating blood regularly also brings various health benefits to the donor. This study aims to increase public understanding about the importance of blood donation through interviews and research at Sunan Giri University, Surabaya. Interview results show that blood donation not only saves lives, but also helps maintain the health of donors and encourages a spirit of mutual cooperation in society. Through education and increasing awareness, more people are expected to be involved in sustainable blood donation activities.